PENGEMBANGAN MODUL VERTEBRATA BERMUATAN HIGH ORDER THINKING SKILL (HOTS) - Haditsa Nurrahma; Husnarika Febriani; Lailatun Nur Kamalia Siregar (JURNAL MANAJEMEN PENDIDIKAN, 2023)
The purpose of this study was to examine the feasibility, practicality and effectiveness of vertebrate materials containing higher order thinking skills (HOTS). The type of research is research and development or R&D. This study uses a 4D model which consists of 4 stages: Define, Design, Develop and Disseminate. The location of the research was conducted at SMA Negeri 1 Seisuka. Data collection techniques used interviews, as well as questionnaires and pretest-posttest tests. The research instrument was in the form of a questionnaire which included 3 types, namely the media expert questionnaire, the module expert questionnaire and the student and teacher participant questionnaire. Information analysis method that is using quantitative and qualitative. In conclusion, the suitability of the material according to type is very feasible with an average score of 83% and 93%. The practicality of the material meets the very instant criteria with an average value of 93% and 90%. The material was seen from the results of the pre-test and post-test in measuring student learning activities, which were reassessed with an average N-Gain value of 0.7. On the other hand, this material was considered quite efficient in improving student learning outcomes, tested with an average score 71%.Â